Assessing the effectiveness of supply chain partnering with scalable partnering as a moderator - Rajagopal, Premkumar; Zailani, Suhaiza; Sulaiman, Mohamed (Emerald Group Publishing Limited, 2009)
Purpose – The primary purpose of this paper is to examine empirically the significant determinant for supply chain partnering (SCP) that can be applied by the firms to increase their effectiveness in SCP efforts. Next, the paper intends to examine the impact of scalable partnering towards the effectiveness of SCP.